Search for the radiative decays D + → γρ + and D + → γK *+ - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
We search for the radiative decays D+ → γρ+ and D+ → γK*+ using 20.3 fb−1 of e+e− annihilation data collected at the center-of-mass energy s = 3.773 GeV by the BESIII detector operating at the BEPCII collider. No significant signals are observed, and the upper limits on the branching fractions of D+→ γρ+ and D+→ γK*+ at 90% confidence level are set to be 1.3 × 10−5 and 1.8 × 10−5, respectively.